Pembuatan keju dengan menggunakan enzim renin Mucor pusillus amobil - Mustakim Mustakim; R. F. Muarifah; Khotibul Umam Al Awwaly (Faculty of Animal Science, Universitas Brawijaya, 2009)
This study was aimed to understand the goog condition of temperature and pH in the cheese making with immobilized rennin enzyme from M. pusillus. Rennin from M. pusillus was produced using corn starch as substrate, incubated at 370C for 116 hours. Immobilization was conducted with entrapment method using alginate. Proteolytic and milk-clotting activities of enzyme was measured. Furthemore, the immobilized enzyme was used in the cheese production with defferent temperatures (32, 37 and 420C) and pH (5.0, 5.5 and 6.0) using Split Plot Design. It was conducted a test of pH, titratable acidity and texture for produced cheese. The result showed that the alginate matrix can be used to immobilized rennin enzyme from M. pusillus. Immobilization of rennin enxyme from M. pusillus has proteolitic activity value 0.1395 unit/ml/minute and milk-clotting activity value 6090 unit/mg protein/minute. The temperatures (32, 37 and 420C) in the cheese making using immobilized rennin enzyme M. pusillus gave a highly significant different effect (P<0,01) on texture and pH of fresh cheese. The pH (5.0, 5.5 and 6.0) gave a highly significant different effect (P<0,01) on pH and titratable acidity of fresh cheese. It is concluded that alginate can be used in the rennin enzyme immobilization. Temperature and pH gave a highly significant different effect on texture, pH and titratable acidity of fresh cheese. The temperature of 370C and pH 6.0 can be used to make a good quality cheese with immobilized rennin enzyme from M. pusilus using alginate with characters as follows : texture 1.1866 N, pH 4.94 – 5.21 and titratable acidity 1.409%.